Romano Guardini : a precursor of Vatican II - Krieg, Robert Anthony, 1946- (University of Notre Dame Press, 2009)
"In Romano Guardini: A Precursor of Vatican II, Robert Krieg tells the story of one of the most creative theologians in the twentieth century, who anticipated Vatican II's commitment to read "the signs of the times." No other volume in the English language offers such a complete portrait of Guardini and his world." "Exploring the context in which Guardini learned and taught, Krieg introduces us to his pastoral leadership, particularly in the liturgical and youth movements. Drawing on the more than 75 books and 100 articles written by Guardini, this book then examines the recurring major themes of his theology: divine revelation as God's self-disclosure, the church as Christian community, liturgy as play in God's presence, literature as expression of religious experience, Nazism as negation of personal existence, Jesus Christ as mediator, and Christian acceptance of modernity." "Although he never intended to promote an ecumenical council of reform, Guardini's career-long commitment to both Judeo-Christian wisdom and intellectual exchange with contemporary thought resulted in his becoming widely regarded as a major precursor of the Second Vatican Council. Respected theologians such as Karl Rahner, Hans Urs von Balthasar, and Cardinal Joseph Ratzinger have acknowledged their indebtedness to him."--BOOK JACKET.